A multilevel study of the relationship between leader agreeable communication style and team creativity: Knowledge sharing as mediator and knowledge ownership as moderator - Sukbong Choi; Jae-Geum Jeong (Global Business & Finance Review (GBFR), 2022)
Purpose: This study investigated the positive effects of a leader agreeable communication style on team creativity and team- and individual-level knowledge sharing. Also verified was the extent to which the level of effect of a leader agreeable communication style on team- and individual-level knowledge sharing varies depending on the team members' self-perception of knowledge ownership, applying a multilevel analysis to concurrently deal with team- and individual-level relations. Design/methodology/approach: The 69 teams consisting of 350 employees were collected from Korean companies. We conducted a multi-level analysis to confirm the effect of the control variables on the relationship between the group level and the individual level, which affects team creativity. Analytical methods were performed by using HLM (Hierarchical Linear and Nonlinear Modeling) 7.01. Findings: The analysis results confirmed the positive effect of a leader agreeable communication style on both team creativity and team- and individual-level knowledge sharing. Team knowledge sharing was found to completely mediate and individual-level knowledge sharing to partially mediate, between leader agreeable communication style and team creativity. Whereas the effect of a leader agreeable communication style on individual knowledge sharing was negatively intensified with the increase in team member's perception of individual knowledge ownership, it yielded insignificant results in terms of team knowledge sharing. Research limitations/implications: This study expanded the understanding of source of team creativity by develop- ing theoretical framework of the relationship between an agreeable leader's communication style and individual and team knowledge sharing and team creativity. Originality/value: This study identified originally an agreeable leader's communication style as an important antecedent variable of knowledge sharing. In addition, by using a multilevel analysis model, this study first found that an agreeable leader's communication style had a significant effect on team creativity through the mediation of individual and team knowledge sharing.
Keywords: 650; Leader agreeable communication style; Knowledge sharing; Perceived team creativity; Psychological knowledge ownership